ANALISIS PENGARUH DEBT TO EQUITY RATIO, CURRENT RATIO DAN RETURN ON INVESTMENT TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Huda, Khoirul; Asakdiyah, Salamatun (Universitas Ahmad Dahlan, 2013)
This research was aimed to know whether there was an influence of Debt to Equity Ratio (DER), Current Ratio (CR), Return on Investment (ROI) towards Dividend Payout Ratio (DPR) in food and beverage companies listed in Indonesian Stock Exchange of 2010-2012 periods. Populations in this research were 18 food and beverage companies listed in Indonesian Stock Exchange of 2010-2012 periods. Sampling technique used a Purposive Sampling. It obtained 10 companies entered in the criteria. The analysis technique used a panel data regression and a hypothesis test using t-test with trust level of 5%, Out of the three independent variables i.e. Debt to Equity Ratio (DER), Current Ratio (CR), Return On Investment (ROI), and Current Ratio (CR) significantly Dividend Payout Ratio (DPR). R-square value was 38.5%.